Hybrid anapole modes of high-index dielectric nanoparticles - Luk'yanchuk, Boris (2018)
We investigate the peculiarities of light scattering from subwavelength particles made of high-refractive-index materials caused by the coexistence of particular anapole modes of both electric and magnetic character. The similarities and differences of such anapole modes are discussed in detail. We also show that these two types of anapole modes can be supported simultaneously by subwavelength high-index spherical dielectric particles.